Melanotic Neuroectodermal Tumor of Infancy: A Case Series and Comprehensive Review of this Rare Pediatric Neoplasm - Dhal, Ipsita; Lali, Bhagat Singh; Chowdhury, Zachariah; Saha, Soumitra (Asian Pacific Journal of Cancer Biology, 2023)
Melanotic neuroectodermal tumor of infancy also known as progonoma is an exceedingly rare neoplasm occurring within first two years of life with around 550 cases reported so far. It is predominantly a benign neoplasm but clinical suspicion of malignancy is always high owing to its rapid progression. Thus, it is a cause of concern to the parents and clinicians alike. It mostly involves the craniofacial bones and mean age of occurrence is 5 months. On radiology, well-defined lytic lesions are encountered. Histopathology is the gold standard for diagnosis wherein a biphasic tumor is seen. It comprises larger polygonal cells with melanin pigment and smaller round blue cells. Surgical excision is the preferred modality of treatment. However, the recurrence rates vary from 15 to 27%. Very few cases with metastasis have been reported. We present two interesting cases of this rare neoplasm along with a comprehensive clinical and pathological review of this rare entity.